HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN PADA BALITA DI DESA BALONGSARI KECAMATAN GEDEG KABUPATEN MOJOKERTO - Eka P, Veryudha; Juli Asri, Dian (JURNAL KEPERAWATAN BINA SEHAT, 2015)
A crucial period in the development of the child is on 1-5 years old. This period is the basis of children’s growth, but it also develop of language skills, creativity, social awareness, emotional intelligence and running very quickly, which is the foundation for furhter development of child. An important part needed is nutrition. Growth and development require six main nutrient, namely carbohydrates, proteins, fats, vitamins, minerals and water. In this case, nutrition is very important for health and intelligence. Malnutrition during this gold is irreversible (can not be recovered). This study would like to determine the relationship of nutritional status to develop of children under five in balongsari gedeg mojokerto regency. The research designed for an analytical cross sectional correlation and sampling was done by cluster random sampling technique. The number of subjects is 129 childrens. The analysis using the spearman rho correlation test. The results showed statistically ρ value 0.005 < α 0.05. The conclusion that can be drawn is that there is a positive and significant association with a low level of correlation between the nutritional status of children under five in Balongsari Gedeg Mojokerto Regency.Keywords:Nutritional Status,Development,Children under five